Corporate Strategy for Generating High Non-Linear Revenues: A Case Study of TCS - Mital , A. K.; Aggarwal , Vimal Kumar (Gyan Management Journal, 2012)
Non Linear revenues have been a focus area for the Indian IT Vendors since past few years and all the Indian IT vendors are looking to delink revenue growth with employee headcount growth. TCS has close to 2,50,000 employees with 2012 fiscal revenue target of US$ 10 billion and strategy to increase employee headcounts for incremental revenues is risky as managing, training, and hiring such huge number of employees is difficult and requires significant monetary and human resources which is not cost effective. Non Linear revenues also help in increasing the revenue per employee, employee productivity, and also the operating margins as non linear models help vendors to charge higher prices for the services. Top Indian IT Vendors have adopted following models Intellectual Property/ Products, Cloud Computing, Platform BPOs, Non Linear Pricing Models, Delivery Accelerators, Branding of products and services/solutions and Merger & Acquisitions to increase the non linear revenues.
Keywords: Non Linear; IT Vendors; TCS; incremental; Products; BPO